1973
DOI: 10.1128/jb.116.1.192-202.1973
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Preliminary Characterization, and Evidence for Regulation of Invertase in Streptococcus mutans

Abstract: Sucrose dissimilation was studied in five strains of Streptococcus mutans. Glucose-adapted strain SL-1 makes acid more slowly from sucrose than from glucose; glucose-adapted strain SL-1 gives diauxie growth kinetics in broth containing limiting amounts of' both glucose and sucrose. Thus, at least part of the sucrose dissimilative system appears inducible. Sucrase activity was identif'ied in the 37,000 x g soluble cell fraction of five strains. Its intracellular location implies the presence of sucrose permease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
46
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 45 publications
8
46
0
Order By: Relevance
“…Homogenate concentration was 10 mg/ml acetate buffer. 28,30,31). The present investigation with plaque homogenate has shown the apparent pH optimum of pH 5.9 for the invertases to be lower than that for the glycosyltransferases.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Homogenate concentration was 10 mg/ml acetate buffer. 28,30,31). The present investigation with plaque homogenate has shown the apparent pH optimum of pH 5.9 for the invertases to be lower than that for the glycosyltransferases.…”
Section: Discussionmentioning
confidence: 46%
“…A feedback regulation of the glycolytic products on the invertase activity is possible, but not proven in reports on invertases from cariogenic streptococci (19,28,30). Only one report on invertase from Aetinomyces viscosus (18) has shown that the enzyme activity was inhibited by fructose-6-phosphate and fructose-1,6-diphosphate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixture of glucose and fructose gave a greater rate of acid production than did the equivalent concentration of sucrose and this indicates that a limidng stage in acid formation may occur at an extracellular sucrose hydrolysis step. Some ofthe sucrose is probably transported by permease systems (27) and the transport process itself could be rate litniting. BIRKHED (3) obtained a similar rate from 0.1 M sucrose compared with a mixture of glucose and fructose, showing that hydrolysis of sucrose is not rate limiting at higher concentrations.…”
Section: Metabolism Of Oligosaccharidesmentioning
confidence: 99%
“…This free sugar may be present because of transport by a mechanism other than the PTS system, or it could be formed as a result of phosphatase action on 2DG-6-phosphate (26). However, this latter process is energetically wasteful, and support for the former proposal comes from the fmding of TANZEK et al (25) that invertase activity can be located intracellularly in Strep, mutans thereby implying that free sugar (sucrose) can be transported into the cell.…”
Section: Discnssiojimentioning
confidence: 99%